2019
DOI: 10.1002/ente.201900137
|View full text |Cite
|
Sign up to set email alerts
|

Edge Formation in High‐Speed Intermittent Slot‐Die Coating of Disruptively Stacked Thick Battery Electrodes

Abstract: In industrial lithium‐ion battery manufacturing, patterned structured electrodes are required due to subsequent processes. In particular, novel and advanced cell stack formation processes cause challenging design requirements for electrode geometry. This work examines the influence of coating speeds up to 50 m min–1 and wet‐film thicknesses up to 400 µm on the coating edge quality. To determine the coating edge quality, the start‐up length in every pattern in the coating direction is compared for different coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…20,44 Experts that expressed knowledge about this process anticipated either an industrialization of highspeed single sheet stacking, where advanced pick-and-place systems are used to increase productivity, 45 or the implementation of roll-to-roll technology such as coil-to-stack, which is characterized by a device that produces the cell stack from three continuously unwinding coils for cathodes, separators, and anodes. 46 All experts expect reductions in the time required to produce the cell stack, and the average value is decreasing from 0.8 s sheet À1 in 2020 to 0.4 s sheet À1 in 2030. In cell conditioning, the consulted experts anticipate productivity in the cost-intensive formation and aging procedures.…”
Section: Process Technology Roadmapmentioning
confidence: 99%
“…20,44 Experts that expressed knowledge about this process anticipated either an industrialization of highspeed single sheet stacking, where advanced pick-and-place systems are used to increase productivity, 45 or the implementation of roll-to-roll technology such as coil-to-stack, which is characterized by a device that produces the cell stack from three continuously unwinding coils for cathodes, separators, and anodes. 46 All experts expect reductions in the time required to produce the cell stack, and the average value is decreasing from 0.8 s sheet À1 in 2020 to 0.4 s sheet À1 in 2030. In cell conditioning, the consulted experts anticipate productivity in the cost-intensive formation and aging procedures.…”
Section: Process Technology Roadmapmentioning
confidence: 99%
“…This implicates that the electrodes, in particularly the primary layer, have to be manufactured with preferably high production throughput. [15,16] Another cost-benefit arises from the application of aqueous slurry formulations due to lower material and postprocessing expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…Rheological investigations allow an insight into the flowability of the slurry, which is crucial for the coating process and the process stability. [36,[38][39][40] To investigate the influence of particle morphology on the electrode production process, slurries were prepared using the same composition and procedure, and the flow behavior was characterized. An overview of the composition of the slurries used for these studies is shown in Table 2.…”
Section: Slurry Composition and Flow Behaviormentioning
confidence: 99%